Experimental Study on the Piezoresistivity of Concrete Containing Steel Fibers, Carbon Black, and Graphene - Wang, Shijun; Singh, Amardeep; Liu, Qiong (Frontiers in Materials, 2021)
Adding conductive materials to cement-based composites can lead to pressure-sensitive properties. In this study, different scales of conductive materials were added into concrete, including macro-scale steel fibers, micro-scale carbon black powder and nano-scale graphene. The coupling effect of three scales of materials ensured that the intelligent concrete had improved strength, lower cost and comparable pressure-sensitive performance. The results show that the strength of intelligent concrete with multi-scale conductive materials is higher than that of the contrast group of ordinary concrete and intelligent concrete with adding nano-scale graphene alone. Especially, the addition of steel fibers significantly improved the crack resistance of the intelligent concrete. In the elastic stage, the resistivity of intelligent concrete with multi-scale conductive materials decreases with the increase of compression, and the decrease range of resistivity is approximately proportional to the external force. After reaching the peak load, the resistivity of the intelligent concrete gradually increases. These studies lay a foundation for the application of intelligent concrete in deformation and damage monitoring.